Epidemiology of football injuries of the German Bundesliga: a media-based, prospective analysis over 7 consecutive seasons - aus der Fünten, K.; Tröß, T.; Hadji, A.; Beaudouin, F.; Steendahl, I. B.; Meyer, T. (Sports Medicine - Open, 2023)
Key Points